Maternal Humoral Immune Responses Do Not Predict Postnatal HIV-1 Transmission Risk in Antiretroviral-Treated Mothers from the IMPAACT PROMISE Study - Hompe, Eliza D.; Jacobson, Denise L.; Eudailey, Joshua A.; Butler, Kevin; Edwards, Whitney; Pollara, Justin; Brummel, Sean S.; Fouda, Genevieve G.; Chinula, Lameck; Kamanga, Melvin; Kinikar, Aarti; Moodley, Dhayendre; et al. (Msphere, 2019)
To design immune interventions that can synergize with antiretroviral therapy (ART) to reduce the rate of HIV mother-to-child transmission (MTCT), it is essential to characterize maternal immune responses in the setting of ART during pregnancy and breastfeeding and define their effect on MTCT. Prior studies reported an association between breast milk envelope (Env)-specific antibodies and antibodydependent cell cytotoxicity (ADCC) activity with reduced postnatal transmission. In this study, we investigated whether these immune correlates were similarly associated with protection in a matched case-control study of mother-infant pairs receiving maternal ART or infant nevirapine prophylaxis during breastfeeding in the International Maternal-Pediatric-Adolescent AIDS Clinical Trials Network Promoting Maternal-Infant Survival Everywhere (PROMISE) trial, assessing postnatal transmission risk in 19 transmitting and 57 nontransmitting mothers using conditional logistic regression models adjusted for maternal plasma viral load. The odds ratios of postnatal MTCT for a 1-unit increase in an immune correlate were 3.61 (95% confidence interval [CI], 0.56, 23.14) for breast milk Env-specific secretory IgA (sIgA), 2.32 (95% CI, 0.43, 12.56) for breast milk and 2.16 (95% CI, 0.51, 9.14) for plasma Env-specific IgA, and 4.57 (95% CI, 0.68, 30.48) for breast milk and 0.96 (95% CI, 0.25, 3.67) for plasma ADCC activity, with all CIs spanning 1.0. Interestingly, although mucosal IgA responses are poor in untreated HIV-infected women, there was a strong correlation between the magnitudes of breast milk and plasma Env-specific IgA in this cohort. In this analysis of the small number of postnatal virus transmissions in the landmark PROMISE study, no single antibody response was associated with breast milk transmission risk.
Keywords: ADCC; HIV-1; Antibodies; Antiretroviral therapy; Breast milk; Postnatal transmission